THE EFFECT OF AIR TRAFFIC CONTROLLER ASSISTANT AVAILABILITY ON AIR TRAFFIC CONTROLLER WORKLOAD: A HUMAN RESOURCE MANAGEMENT PERSPECTIVE - Radhinal Oricho Meisida; Imam Sonhaji; Martha Saulina (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
The increasing intensity of air traffic has a direct impact on the workload of Air Traffic Controllers (ATCs), who serve as key human resources within air navigation service organizations. Previous studies on ATC workload have predominantly emphasized technical and operational aspects related to aviation safety, while managerial and organizational perspectives—particularly those concerning human resource support—remain relatively limited. This study aims to examine the effect of the availability of Air Traffic Controller Assistants (ATCAs) on the workload of Air Traffic Controllers from a human resource management perspective. This research employed an explanatory design using a quantitative approach. Data were collected through a survey of 64 Air Traffic Controllers assigned to the Approach/Terminal unit. ATC workload was measured using the NASA Task Load Index (NASA-TLX), while the availability of ATCAs was assessed using a structured questionnaire. Data analysis was conducted through descriptive statistics, assumption testing, and simple linear regression using SPSS software. The results indicate that the availability of ATCAs has a statistically significant effect on ATC workload (p < 0.05), although the magnitude of this effect is moderate. These findings suggest that human resource support through the management of support personnel plays an important role in influencing workload, particularly in work environments characterized by high cognitive demands and time pressure. This study concludes that managing the availability of ATCAs should be considered an integral component of human resource management strategies aimed at enhancing work effectiveness and organizational sustainability within air navigation service organizations.